Peran Ekspresi Wajah Dalam Membangun Komunikasi Non Verbal Bagi Anak-Anak Dengan Autisme - Marcha, Audry (Prisani Cendekia Institute, 2024)
Autism is a spectrum of developmental disorders that often make it difficult for individuals to communicate. Verbal communication in children with autism is often hampered, requiring a holistic approach to support more effective understanding and delivery of messages. This study aims to examine the role of facial expressions in supporting verbal communication in children with autism. The research method involves in-depth observation of the facial expressions of children with autism in everyday communication situations, supported by detailed analysis of the verbal interactions that occur. The data collected is interpreted to understand how facial expressions can be an important tool in strengthening and complementing verbal communication that may be limited. The results showed that facial expressions, including various facial expressions and emotions, play a significant role in supporting the understanding and interpretation of verbal messages in children with autism. The interaction between facial expressions and verbal communication shows a close relationship, where non-verbal expressions can communicate nuances and meanings that may be difficult to express verbally.